2005
DOI: 10.1111/j.1368-5031.2005.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating leptin and body composition in chronic obstructive pulmonary disease

Abstract: Nutritional depletion and weight loss are two features of chronic obstructive pulmonary disease (COPD), and the association between low body mass index (BMI) and poor prognosis in patients with COPD is a common clinical observation. Mechanisms of weight loss are still unclear in COPD. Excessive energy expenditure partly due to increased work of breathing was shown, but other mechanisms have been searched for. Leptin is a hormone secreted by adipocytes that plays an important role in energy homeostasis and regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
3
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
(24 reference statements)
2
12
3
2
Order By: Relevance
“…Comparison of body composition, endocrine and biochemical parameters according to the presence of hyperinflation associated with a decrease in body mass index and lean body mass. In addition, it supports the notion that weight loss in COPD patients does not lead to an increase in circulating leptin levels but contrarily leptin remains at certain levels as compensatory mechanism to preserve lean body mass in COPD patients (14).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Comparison of body composition, endocrine and biochemical parameters according to the presence of hyperinflation associated with a decrease in body mass index and lean body mass. In addition, it supports the notion that weight loss in COPD patients does not lead to an increase in circulating leptin levels but contrarily leptin remains at certain levels as compensatory mechanism to preserve lean body mass in COPD patients (14).…”
Section: Discussionsupporting
confidence: 75%
“…In another study serum leptin levels were found to be low in COPD patients with a low BMI (14). Moreover, it was claimed that weight loss in COPD patients does not cause an increase in leptin levels, but contrarily leptin remain at certain levels as a compensatory mechanism to preserve lean body mass in COPD patients (14).…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, in our meta-analysis, circulating leptin levels were correlated with nutritional parameters in COPD patients. Four articles [17,30,35,44] reported that circulating leptin levels decreased in COPD patients with lower BMI compared to healthy controls, which was not consistent with the small study of Takabatake et al [31], who reported that no difference was found between stable COPD patients and healthy controls. In addition, there was no difference in either circulating leptin levels or BMI between noncachexic COPD patients and healthy controls.…”
Section: Discussionmentioning
confidence: 35%
“…24 The chronic elevation of inflammatory cytokine levels, which disrupts normal hormonal secretion and peripheral tissue substrate metabolism, is the main cause of such alterations. 25 Several reports 26 have described reduced leptin levels in stable patients compared to control subjects, in accordance with a low body mass index and FM. On the contrary, leptin levels appeared to be increased and directly correlated to inflammatory cytokine levels, causing nutritional decay, in unstable or exacerbated patients.…”
Section: Discussionmentioning
confidence: 99%